Respons Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) Varietas Bima Brebes Terhadap Berbagai Dosis Trichoderma sp. - Nur Halizah; Pandu Sumarna; Faisal Al Asad; Yudhi Mahmud; Fina Dwimartina; Eli Fatimah (Jurnal Agro Wiralodra, 2026)
Shallots are a horticultural commodity in Indonesia with high economic value. This spice vegetable plays a very strategic role. The demand and demand for shallots always increase every year, but production has not been matched. This study aims to determine the effect of Trichoderma sp dosage on the growth and yield of shallots. This research was conducted in rice fields in Pekandangan village, Indramayu Regency, from June to August 2025. The experimental design used in this study was a Randomized Block Design (RBD) consisting of five treatments, each replicated five times. The five Trichoderma sp. dosage treatments were T0=0, T1=10kg/ha, T2=20kg/ha, T3=30kg/ha, T4=40kg/ha. The result of the study of various doses of Trichoderma sp showed a significant effect on the parameters of plant height, number of leaves, tuber diameter and root length, the highest in the T3 treatment, namely 30kg/ha. However there was no significant effect on the yield parameters of shallots wet and dry tuber weight.